2016
DOI: 10.1155/2016/9271434
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Rockburst Tendency and AE Characteristics of Inhomogeneous Coal-Rock Combination Bodies

Abstract: In order to research the influence of homogeneity on the rockburst tendency and on AE characteristics of coal-rock combination body, uniaxial compressive tests of inhomogeneous coal-rock combination bodies obeyed by the Weibull distribution were simulated using particle flow code (PFC2D). Macromechanical properties, energy evolution law, and AE characteristics were analyzed. The results show that (1) the elastic modulus homogeneitymEhas an exponential relation with macroscopic modulusE, and the bonding strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Under the action of external load, cracks will occur in coal and rock mass, and stress waves will be released in the process of crack propagation, that is, the so-called acoustic emission phenomenon. Many scholars monitor the crack propagation in the coal and rock loading process by acoustic emission-charge signal, as an auxiliary means to study the mechanical properties of coal-rock mass [12][13][14][15]. For example, Tan et al [14] studied the influence of homogeneity on the rock-burst tendency and on AE characteristics of coal-rock combination body, and the result show that the more inhomogeneous the coal-rock combined body is, the shorter the lasting time in the active period of AE characteristics will be.…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of external load, cracks will occur in coal and rock mass, and stress waves will be released in the process of crack propagation, that is, the so-called acoustic emission phenomenon. Many scholars monitor the crack propagation in the coal and rock loading process by acoustic emission-charge signal, as an auxiliary means to study the mechanical properties of coal-rock mass [12][13][14][15]. For example, Tan et al [14] studied the influence of homogeneity on the rock-burst tendency and on AE characteristics of coal-rock combination body, and the result show that the more inhomogeneous the coal-rock combined body is, the shorter the lasting time in the active period of AE characteristics will be.…”
Section: Introductionmentioning
confidence: 99%
“…e result showed that the vibrational signals recorded before impact-induced failure exhibit remarkable precursory characteristics indicative of a rock burst. Tan et al [27] explored the effect of the homogeneity of a CR combined body on AE energy by PFC numerical simulation software. e result indicated that the stronger the homogeneity of coal and rock masses, the larger the rock burst tendency of a CR combined body.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [21] conducted a true-triaxial unloading test on limestone with acoustic emission monitoring and researched the relationship between the characteristics of rock burst and AE parameters. Tan et al [22] found that the AE characteristics can be used to predict the rock burst tendency of the coal-rock combination body. The Kaiser Effect [23] and Felicity Effect [24] of rock were found and used to reflect the damage and failure characteristics of rock materials [25,26].…”
Section: Introductionmentioning
confidence: 99%